P620 Inclusivity, exclusivity, stability and prospective testing of two real-time PCR assays for mycoplasma genitalium. (14th July 2019) - Hardick, Justin; Tan, Litty; Ingles, Cassandra; Denver, Colin; Pol, Barbara Van Der; Jensen, Jorgen; Trent, Maria; Gaydos, Charlotte
Abstract : Background: Mycoplasma genitalium (MG) is an emerging sexually transmitted infection. It has been associated with cervicitis and PID in women and urethritis and persistent NGU in men. Methods: We evaluated two MG qPCRs, 16S rRNA and pdhD. The limit of detection (LOD) for the 16S rRNA and pdhD assays were determined with 11 MG strains. Inclusivity/exclusivity testing was performed with 11 MG strains and 43 non-MG strains. Stability testing was performed with mock vaginal and urine samples stored at +4°C and 25°C at 1.5X, 4X, 10X and 20X LOD at 0, 7, 14, 21, 28 and 35 days. These assays were employed in an ongoing prospective study examining the prevalence of MG in symptomatic and asymptomatic men and women. Positives were sequenced to determine mutation rates in the 23S rRNA gene conferring macrolide resistance. Results: The pdhD and 16S assays had LODs of 1324 and 1536 copies/ml, respectively. All inclusivity/exclusivity testing performed as expected. Detection in urine and vaginal matrix at 4°C was 100% for both assays. Detection in urine at 4°C was 100% for both assays while detection in urine at 25°C was 100% at 28 days, but was 90% at 35 days. For symptomatic men, the prevalence was 19% (4/21) and 14.3% (3/21) for the pdhD and 16S rRNA assays respectively, and was 7.14% (1/15) in symptomatic women for both assays. There were no MG detections in asymptomatic subjects. Of the positives, 100% (5/5) were determined to be 23S mutants. Conclusion: Both assays had reasonable LODs and expected results for inclusivity/exclusivity testing. For stability testing, results were as expected up to 35 days, where a loss of positivity was observed for urine samples. We observed a high prevalence of MG in symptomatic men and women, as well as a high percentage of 23S mutants conferring macrolide resistance. Disclosure: No significant relationships.